Interest in online information about cigarettes and tobacco among adolescents - Gazibara, Tatjana; Cakic, Milica; Cakic, Jelena; Grgurevic, Anita; Pekmezovic, Tatjana (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. While growing up, adolescents find themselves in various situations, where they are exposed to harmful factors, such as tobacco and psychoactive substances (PAS). Expectedly, they might want to know more about them, but are often not willing to ask anyone in person. Aim. To explore the prevalence and factors associated with the online information seeking about tobacco smoking in a sample of high school students. Study design. Cross-sectional. Methods. This study included 702 students from four public high schools in Belgrade, Serbia. Data were collected by using an anonymous questionnaire on socio-demographic characteristics, use of online platforms and interest in topics such as cigarettes/ tobacco, psychoactive substances and fitness. The study outcome was opting for cigarettes/tobacco as a topic when searching for online information. Electronic health literacy was examined by the electronic health literacy. Results. The prevalence of online information seeking about cigarettes/tobacco was 9.4% (66/702). Having a lower grade point average, having parents of a higher education level, using social media and websites run by health institutions and searching for information about psychoactive substances online were independently associated with the online information seeking about cigarettes/tobacco. Conclusion. To help high school students understand health-related implications of tobacco exposure, it would be useful to provide hands-on education about tobacco in high schools. These could include online learning platforms, such as websites run by health institutions and social media. Addressing tobacco in the context of health education in high schools might be relevant for future health behavior.